ECOPSYCHOLOGICAL EDUCATIONAL ENVIRONMENT OF STUDENTS OF THE NEW UKRAINIAN SCHOOL - Atamanchuk, Nina (SWorld-Ger Conference proceedings, 2025)
The article examines the theoretical aspects of ecopsychology, as well as practical methods and strategies aimed at developing environmental competence among students at the primary education level. The significance of the ecopsychological approach in sha